Engineering Service-Learning: A Model for Preparing Students for Engineering Practice while meeting Needs of the Underserved - Oakes, William; Zoltowski, Carla B.; Huff, James (Journal of Engineering Education Transformations, 2014)
Preparing tomorrow's global engineering leaders requires a strong technical foundation as well as a broad set of professional skills. Integrating these into the undergraduate curriculum can be challenging within traditional courses. One approach that has shown success is service-learning, which engages students in meetings needs of local or global communities. An engineering exemplar of service-learning approach is the EPICS (Engineering Projects in Community Service) Program founded at Purdue University and disseminated to more than 20 other universities. This paper describes the EPICS model and how it has been disseminated and discusses data on student perception and learning.